Two variations of the anterior communicating artery: A clinical reminder - (:unkn) unknown (My University, 2004)
Of the 30 cadavers we examined two unusual variations of the anterior communicating artery (ACoA) were observed. In the first case ACoA was duplicated with a fenestrated anterior cerebral artery (ACA). In the second case, an oblique ACoA was present. Further, two branches of the oblique ACoA were joined the right ACA. The clinical significance of the cases has been disscussed. © neuroanatomy.org.
Keywords: Anterior cerebral artery; Anterior communicating artery; Duplication; Fenestration; Variation